SÍNTESE DE PIGMENTOS A BASE DE SnO2 DOPADO COM Fe2O3 - Schmidt, Samara (2012)
In this work a Fe(III)-doped tin oxide (SnO2) system using chemical mixture of SnO2 and Iron(III) nitrate nonahydrate (Fe(NO3)3. 9H2O). This system was calcined at temperatures from 600 ºC to 1200 C. The as-calcined powders were characterized using several techniques: thermal analysis (DTA/TG) to identify the thermal stability;X-ray diffraction to identify the resulting phases; scanning electron microscopy and photocorrelation spectroscopy to study the material morphological structure. The usefulness of the ceramic pigment was evaluated testing the solubility of the oxide system in frit and its color stability. Also, using UV-visible diffuse reflectance spectroscopy, the CiELab* coordinates of the system were estimated.